Ionic Liquid-Mediated, Rapid N-Alkylation of Heterocyclic Compounds with Trialkyl Phosphites in the Presence of Dialkyl Acetylenedicarboxylates - Alireza Hassanabadi; Mohammad H. Mosslemin; Mohammad Anary-Abbasinejad; Azadeh Kalantarinejad; Mozhdeh Jerjisi Shirazi (E-Journal of Chemistry)
Ionic liquids such as 1,3-dialkylimidazolium bromides and make excellent solvents for N-alkylation of heterocyclic compounds such as saccharin and rhodanine with trialkyl phosphites in the presence of dialkyl acetylenedicarboxylates.